Nurse-led telehealth intervention effectiveness on reducing hypertension: a systematic review - Maria Kappes; Pilar Espinoza; Vanessa Jara; Amanda Hall (BMC, 2023)
Abstract Background Hypertension is a public health concern for many countries. The World Health Organization has established a global objective to reduce the prevalence of non-communicable diseases, including hypertension, which is associated with cardiovascular disease. Remote nursing interventions can potentially lessen the burden on the healthcare system and promote a healthier population. This systematic review aims to synthesize available evidence on the effectiveness of nursing-led telehealth interventions in reducing blood pressure in hypertensive patients. Methods A systematic review was conducted. The search was performed from May to June 2021, in the databases: PubMed, Scopus, Cochrane Library, Web of Science, CINAHL, and ProQuest within 2010-2021 in English, Spanish and Portuguese. Randomized controlled trials and Quasi-experimental studies were considered. This systematic review followed the criteria of the Cochrane Handbook for Systematic Reviews of Interventions, with the support of the PRISMA guidelines and registered in PROSPERO. For critical analysis, the tools of the Joanna Briggs Institute were used. Results Of the 942 articles found, six controlled clinical trials and one quasi-experimental study were selected. Different nurse-led interventions (telehealth devices, remote video consultation, calls and email alerts) have demonstrated a significant decrease in blood pressure (especially systolic blood pressure) in the intervention groups. Nurse-led interventions also effect hypertension awareness, self-efficacy, and self-control. Positive effects on lowering cholesterol, consumption of fruits and vegetables, physical activity and adherence to medication were also described. Conclusion Nurse-led interventions delivered remotely have a positive effect in lowering the blood pressure of patients with hypertension. Further research is required to support strategies that will deliver the best continuous, quality, and cost-effective nursing care.